Reconstruction of peaceful civilisation in asean countries based on al wasatiyyah oriented education ( presented on behalf of Tan Sri Mohd Kamal Hassan). - Ismail, Nik Ahmad Hisham; Hassan, Mohd. Kamal (2016)
Peaceful civilization as deem appropriate to the education system in the asean countries based on the Alwasatiyyah concept.